Full duodenal rupture after direct abdominal trauma in soccer: a case report of an elite soccer player with follow up and return to play protocol - Hassanmirzaei, B.; Fahimipour, F.; Khosravi, A.; Barghi, T. S. (Science and Medicine in Football, 2021)
Severe traumatic abdominal injuries and duodenal ruptures are relatively rare in soccer and can be easily missed and turn into a life-threatening condition. All team physicians need to be familiar with the warning sign in these situations. This report aims to report a case, discuss the diagnostic and treatment process and the return to play protocol. During a professional female soccer team training session, the injury occurred while the player`s epigastrium was hit hardly by the opponent`s knee. In the first evaluation, there was only mild epigastrium pain without any other sign. Eventually, pain exacerbated, nausea and vomiting were added. All the initial evaluation (Physical examination, abdominal X-ray, ultrasonography, blood tests) were normal. Eventually, she developed abdominal guarding and underwent abdominopelvic computed tomography with intravenous contrast where Duodenal rupture becomes evident. She underwent laparotomy and full duodenal repair and discharged from the hospital in good health. For the return to play determination in such injuries, the abdomen should not be imposed on any trauma for about 6 months, so while the player can start a self-training session firstly without a ball and then with a ball, she is not allowed to play or train with others for 6 months.